Formação continuada e práticas docentes em educação ambiental no contexto do semiárido paraibano - Ruffo, Thiago Leite de Melo (2016)
The main question of the present research is to investigate whether the continuing education of teachers in Environmental Education (EE), developed in a critical/emancipatory perspective, interdisciplinary and contextualized with local reality, makes possible the exercise of this in formal education, focusing on the sustainability of Biome Caatinga and living with the semi-arid. Thus, this study has as general objective to analyze the process of continuous training of teachers in EE in the cariri and the implications in their teaching practice. The thesis is that training teachers-researchers, authors of their own practices, contributes to the continuous and permanent work of the EA in a critical/emancipatory, interdisciplinary and contextualized perspective with the Semiarid. The work is theoretically supported by authors such as Freire; Tardif; Fazenda; Pimenta; Layrargues; Lima; Loureiro; Abílio and had the universe surveyed 20 teachers from five cities and 12 different schools of cariri. The research approach was mainly qualitative and was guided by the assumptions of Collaborative Research. In monthly meetings during the year 2015, the target teachers of research were followed in situ, where data from your teaching practice were collected through interviews, activity reports and monitoring reports, which were analyzed using the technique content analysis. The results showed that the continued training of teachers for the Semiarid possible that EE was worked continuously and permanently in the school context of cariri. It was noticed that some teachers still work EE in isolation, disciplinary manner. However, many attempts and some successful experiences were observed with regard to interdisciplinarity, as recommended by the literature on the subject. As for the trend of EE more addressed the practices of teachers investigated, the results point to many actions that are used the theoretical framework of Critical EE to carry out their actions. About contextualization of teaching actions, we were observed that these to perform in several aspects - environmental, social, economic, cultural; thus opens a space for the construction of a contextualized curriculum with the semiarid region in these schools. To strengthen contextualized education, it is necessary not only to understand the limits and semiarid region's potential, but building knowledge for the modification of that reality, guided by the perspective of coexistence and considering people as knowledge producers. We walked thus to the need to rethink and outline strategies to enhance the human being as an essential part of any educational proposal.